Analyzing factors promoting teachers’ use of Lirmi: a digital monitoring system in Chile using the technology acceptance model - Silva, Lucas; Tagle, Maritté; Loncomil, Isabel (Frontiers in Education, 2025)
Digital assessment data’s increasing prevalence in schools offers a powerful tool to enhance educational outcomes, yet its adoption by teachers varies widely. For the first time, an extended version of the Technology Acceptance Model (TAM) was used in a Chilean sample to explore the factors that explain teachers’ use of digital assessment data. An online survey was conducted with 319 teacher users of Lirmi, a consolidated online educational platform with a student assessment module. Using Structural Equation Modeling (SEM), we found that TAM remains a robust and parsimonious framework for explaining teachers’ adoption of digital monitoring systems in a global southern country. While attitudes toward using the system, intention to use it, and perceived usefulness emerged as key predictors (consistent with prior TAM studies) the study provides novel insights by validating TAM in a real-world K-12 educational setting with a commercial product. Importantly, facilitating conditions were found to explain perceived ease of use, and subjective norms significantly influenced perceived usefulness, underscoring the role of infrastructure and peer influence. The results highlight the need for policymakers, school administrators, and ed-tech providers to ensure proper support to foster teachers’ adoption of digital monitoring systems. By extending TAM’s applicability to the Chilean context, this study contributes to understanding how teachers adopt digital tools for assessment in a specific national setting that remains underexplored in the literature.